The Impact of Green Human Resources Managerial Practices on Environmental Sustainability: Evidence from Garments Industry of Bangladesh - Aziz, Farhana Ferdousi; Yasmin, Farhana; Sultana, Tahmina (Asian Journal of Empirical Research, 2020)
The purpose of this paper is to find out the impact of Green Human Resources managerial practices on environmental sustainability in the garment factories of Bangladesh. A combination of qualitative and quantitative methods is used for data collection. The survey respondents were mid-level HR managers of 60 garment factories located in Gazipur. The regression analysis and ANOVA are applied for empirical investigation. The results revealed that four variables have a significant relationship with the dependent variable and that lack of appropriate measures and knowledge is the main reasons for low environmental sustainability. The research identifies the measures that need to be taken and it also claims that there should be awareness of the significance of environmental sustainability among managers and the workforce to achieve environmental sustainability. This is important for Bangladesh, because environmental sustainability has a positive impact on the economy of the country.